Diffusive–thermal oscillations of rich premixed hydrogen–air flames in a microflow reactor. Issue 2 (3rd March 2016) - Miroshnichenko, Taisia; Gubernov, Vladimir; Maruta, Kaoru; Minaev, Sergei
Abstract : In this paper the dynamics of rich hydrogen–air flames in a microflow reactor with controlled temperature of the walls is investigated numerically using the thermal-diffusion model with two-step kinetics in one spatial dimension. It is found that as the parameters of the system are varied the sequence of bifurcation occurs leading to the formation of complex spatio-temporal patterns. These include pulsating, chaotic, mixed-mode and FREI (Flames with Repetitive Extinction and Ignition) oscillations. The critical parameter values for the existence of different dynamical regimes are found in terms of equivalence ratio and flow velocity.